2018
DOI: 10.1002/jcp.26455
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 receptor 2 regulates the proliferation, migration, and barrier integrity of bronchial epithelial cells

Abstract: The airway epithelium plays a crucial role in the pathogenesis of asthma. The functions of leukotriene B4 receptor 2 (BLT2) on the airway epithelial cells remains unknown. In our study, BLT2 expression in 16HBE bronchial epithelial cells were manipulated by transfection with BLT2 overexpression plasmid or BLT2 small interference RNA. 16HBE cells were then exposed to BLT2 antagonist (LY255283) or BLT2 agonist (12(S)-hydroxyheptadeca-5Z,8E,10E-trienoic acid [12-HHT] or CAY10583). The results showed that BLT2 ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Current knowledge of CYP2S1 in endogenous function is largely related to eicosanoids metabolism, and some of its metabolic products have been identified, including 12-HHT, 5-oxo-eicosatetraenoic acid (5-oxoETE), 12-oxoETE, 15-oxoETE, etc. 12 Some of them have been demonstrated to be involved in tumor progression, such as 12-HHT and 5-oxoETE, 33,34 as supported by our data that CYP2S1 knockdown in BCPAP and 8505C cells dramatically reduced 12-HHT levels, and the restoration of 12-HHT could partially reverse inhibitory effect of CYP2S1 knockdown in cell viability. Besides, our data demonstrated that BRAF V600E promotes CYP2S1 transcription by activating MAPK/ERK cascade.…”
Section: Discussionsupporting
confidence: 69%
“…Current knowledge of CYP2S1 in endogenous function is largely related to eicosanoids metabolism, and some of its metabolic products have been identified, including 12-HHT, 5-oxo-eicosatetraenoic acid (5-oxoETE), 12-oxoETE, 15-oxoETE, etc. 12 Some of them have been demonstrated to be involved in tumor progression, such as 12-HHT and 5-oxoETE, 33,34 as supported by our data that CYP2S1 knockdown in BCPAP and 8505C cells dramatically reduced 12-HHT levels, and the restoration of 12-HHT could partially reverse inhibitory effect of CYP2S1 knockdown in cell viability. Besides, our data demonstrated that BRAF V600E promotes CYP2S1 transcription by activating MAPK/ERK cascade.…”
Section: Discussionsupporting
confidence: 69%
“…Restoration of bronchial epithelial barrier is crucial to the management of asthma 61 . The functions of leukotriene B4 receptor 2 on the airway epithelial cells have been recently discovered, and leukotriene B4 receptor 2 antagonists inhibit epithelial permeability, while promoting TJ protein levels of both occludin and claudin‐4 62 . Recent discoveries have revealed the protective effect of airway microbiome, such as that of CpG‐DNA against allergic airway inflammation 63 .…”
Section: Tight Junction In Asthmamentioning
confidence: 99%
“…Although one 5-LO inhibitor, zileuton, is approved for treatment of asthma [51], interference with other molecules in LT biosynthesis and signaling pathway means that it is not fully effective. Roles for BLT2 in asthma have been reported, although to a lesser extent than that of BLT1 [49,52,53,54].…”
Section: Lts and Allergic Diseasesmentioning
confidence: 99%
“…A recent in vivo study in BLT2-deficient mice indicates that BLT2 protects against allergic airway inflammation and that reduced expression of BLT2 by CD4 + T cells might contribute to the pathophysiology of asthma [52]. Also, an increasing number of studies have demonstrated that BLT2 has a protective role in allergic airway inflammation [49,53,54].…”
Section: Lts and Allergic Diseasesmentioning
confidence: 99%